Toward Strained Pillar[4]arene Derivatives - Liu, Ke; Liu, Zhe; Chen, Xue; Liu, Yang; Guo, Qing-Hui (Synlett, 2025)
Over the past decade, pillar[n]arenes have emerged as prominent macrocyclic hosts in supramolecular chemistry owing to their straightforward synthesis, versatile functionalization, and rigid columnar cavities, attracting considerable research interest. However, conventional Lewis acid-catalyzed cyclizations exhibit an inherent preference for larger pillar[n]arenes (n ≥ 5) due to kinetic and thermodynamic factors associated with the dynamic oligomerization process, thereby precluding the synthesis of strained pillar[4]arene architectures. To overcome this challenge, we developed an innovative strain-engineering strategy—from low to high strain—based on a key thiophene-to-benzene transformation. This approach involves stepwise thiophene oxidation followed by an inverse electron-demand Diels–Alder (IEDDA) reaction, dynamically driven by SO₂ extrusion. High-resolution mass spectrometry confirmed the formation of tetrahydro-pillar[4]arene derivatives in the reaction mixture through their characteristic isotopic patterns. Our work establishes a viable route to challenging, strained pillar[4]arenes.
Keywords: Pillar[4]arene; Strained macrocyclic arenes; Dynamic-driven transformation; Inverse electron-demand Diels–Alder reaction